True Crime and Television Archives. Mediation, Re-Enactment, and Self-Reflexivity in Post-2010 True Crime TV Series - Casiraghi, Alessia Francesca; Cenni, Diletta (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
Within the true crime genre, archives play a crucial role – not merely as sources but as dynamic elements that shape the genre’s identity, contradictions, and narrative strategies. This paper explores how post-2010 television true crime series engage with television archives, questioning their function as repositories of information, tools for entertainment, and instruments of media self-critique. Focusing primarily on the tv series, Dove nessuno guarda (Sky, 2023), the study proposes a taxonomy of archival sources – national and local television archives; trial proceedings, which transition from personal or judicial archives to television archives. Finally, this study examines how, in contemporary true crime series, television archives themselves become subjects of storytelling, interrogating the media’s role in shaping public perception. Through a self-reflexive approach, these narratives position television archives as evidence in a broader discourse on media responsibility and truth-making processes.